EVALUATING PEATLAND FIRE MANAGEMENT STRATEGIES USING ASEAN FRAMEWORK: A CASE STUDY OF FMU KAYU TANGI, INDONESIA - Nasruddin Nasruddin (GeoEco, 2026)
Deforestation in South Kalimantan has increasingly encroached upon peatlands within the Kayu Tangi Forest Management Unit (FMU/KPH) in Liang Anggang Sub-district, Banjarbaru City. Despite its designation as a protected forest area, ongoing encroachment and land-use conversion have heightened wildfire risks, with 140 hotspots recorded between 2015 and 2025, averaging 14 hotspots per year. This study aims to analyse the strategic management practices of the FMU-Kayu Tangi based on the ASEAN peatland fire management guidelines and subsequently develop a conceptual model for peatland fire management as an adaptive, collaborative, and sustainable fire control system. A qualitative approach was employed using in-depth interviews, observation, and document analysis. The development of management strategies was guided by the peatland fire management framework published by the Association of Southeast Asian Nations (ASEAN) in 2021 and strengthened through SWOT analysis. The findings reveal that FMU Kayu Tangi implements an integrated peatland fire management approach covering prevention, preparedness, response, and recovery strategies. Preparedness efforts include early warning systems, public campaigns, and information dissemination, while response strategies involve collaboration with the Regional Disaster Management Agency (BPBD), the Indonesian National Armed Forces (TNI), and the Indonesian National Police (POLRI). Recovery strategies focus on post-fire rehabilitation, peat-endemic plant cultivation, burned-area monitoring, and law enforcement. Conceptually, this study identifies the Management Strategy of Peatland Fire (MSPF) as a model integrating regulations, peatland management, community participation, institutional capacity, public communication, and fire-monitoring technology. The study concludes that collaborative, ecosystem-based governance can enhance the effectiveness of peatland fire management despite institutional resource constraints.